KINERJA GURU BAHASA INGGRIS DI SMP DAN SMA MANADO INDEPENDENT SCHOOL (MIS) - Kesek, Kristin Emma; Marentek, Andriyani; Lasut, Theresia M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis research entitled â€œEnglish Teacher Performances in the Middle and High Schools of Manado Independent School (MIS)â€ aims to determine the performance of English teachers in planning, implementing and evaluating English learning in bilingual school, as well as knowing the factors that influence the teacher performances. This type of research is descriptive. The theory used to classify performance of teachers is Usmanâ€™s (2003) theory, and to determine the factors that influence performances of teachers, Tehseen and Hadi (2015) is applied. The research participants were 6 English teachers (3 teachers in Middle School and 3 teacher in High School). Data were collected by using observation and interview methods. The results of this study indicate that teacher performance is very competitive, each teacher tries to apply the best way in planning, implementing and evaluating the learning process. Factors that influence the performance of teachers are divided into two parts: 1) General factors that include: a) teacher salary, b) working condition, c) studentsâ€™ behavior, d) relation among the staffs, e) facilities. 2) Special factors, which are the challenges of teacher performances, including: a) time allocation, and b) studentsâ€™ ability._______________________Keywords : English Teacher, Performance, Factors Influence